Adaptation and validation of the PEDSQL™ oral health scale for toddlers in Chilean population - Claudia Atala-Acevedo; Carlos Zaror; Gerardo Espinoza-Espinoza; Patricia Muñoz-Millán; Sergio Muñoz; María José Martínez-Zapata; Montse Ferrer (BMC, 2020)
Abstract Background The Pediatric Quality of Life Inventory™ (PedsQL™) Oral Health Scale was developed to measure oral health-related quality of life (OHRQoL). The aim of this study was to cross-culturally adapt the parent-reported version for toddlers of PedsQL™ Oral Health Scale into Spanish and to assess the acceptability, reliability and validity of this version in Chilean preschool population. Methods The PedsQL™ Oral Health Scale for toddlers was cross-culturally adapted for the Spanish language using the recommended standards. To assess metric properties, a cross-sectional study was carried out with 301 children aged 2 to 5 years in Carahue, Chile. Chilean versions of the PedsQL™ Oral Health Scale, PedsQL™ 4.0 Generic Core Scales, and Early Childhood Oral Health Impact Scale (ECOHIS) were completed by the children's parents. Dental caries, malocclusion and dental trauma were examined by trained dentists. The PedsQL™ Oral Health Scale was administrated a second time 14-21 days after. The reliability of the scale was verified by analysis of internal consistency (Cronbach's alpha) and reproducibility (Intraclass correlation coefficient - ICC). The validity of the construct was assessed by confirmatory factor analysis and known groups method. The convergent validity was assessed by calculating the Spearman's correlation with the ECOHIS questionnaire. Results The PedsQL™ Oral Health Scale demonstrated good reliability, with Cronbach's alpha coefficient of 0.79 and ICC of 0.85. A moderate-to-strong correlation was found between the PedsQL™ Oral Health Scale and the ECOHIS questionnaire (− 0.64); the PedsQL™ Oral Health Scale score was lower in children with poor than those with excellent/very good oral health (median 100 vs 85, p < 0.001); it also was lower in children with caries than in those caries-free (median 100 vs 90, p < 0.001). No statistically significant differences were found among groups according to malocclusion and traumatic dental injuries. Conclusions The PedsQL™ Oral Health Scale for toddlers in Spanish showed to be equivalent to the original version, and its psychometric properties were satisfactory for application in a Chilean pre-school population.